Characterization of SET/I2PP2A Isoforms in Dogs - YABE, Ryotaro (The Japanese Society of Veterinary Science, 2014)
SET is an endogenous protein phosphatase 2A (PP2A) inhibitor and is associated with a poor prognosis in human leukemia. Previously, we reported increased SET protein levels in canine lymphoma cell lines and the potential therapeutic application of SET antagonists in canine lymphoma. Here, we found that canine cells express several isoforms of the SET protein. We cloned 4 isoforms of SET, named SETα, β, γ and δ. Genomic BLAST showed that the SET genes are located on chromosomes X, 7, 1 and 8, respectively. An immunofluorescent study showed nuclear localization of SETα and β, and nuclear and cytosolic localization of SETγ and δ. We confirmed that SETα and β possess the ability to associate with PP2A. Our data reveal the existence of unique SET isoforms that should be taken into account in SET-targeting drug development studies in dogs.